(untitled) (Journal of Computational Mathematics, 1999)
This paper deals with the stability analysis of numerical methods for the solution of delay differential equations. We focus on the behaviour of three θ-methods in the solution of the linear test equation u'(t)=A(t)u(t)+B(t)u(τ(t)) with τ(t) and A(t), B(t) continuous matrix functions. The stability regions for the three θ-methods are determined.